Rights and responsibilities in the social security system - Griggs, J; Bennett, F (Social Security Advisory Committee, 2009)
This paper was produced in support of advice offered to the Secretary of State in accordance with the Committee's remit (s 170(i) (a) of the SSA 1992 refers). The paper was prepared by independent researchers at the Department of Social Policy and Social Work, University of Oxford (Dr Julia Griggs and Ms Fran Bennett), working to a commission by SSAC. The paper draws on a discussion of relevant issues with SSAC stakeholders at the Committee’s annual Stakeholder Seminar in November 2008.